582 Transperineal Prostate Biopsies: Complication Rates and Predictors of Significant Malignancy. (19th August 2022) - Maikovsky, Z; Gan, C
Abstract: Aim: To ascertain the risks of undergoing a transperineal biopsy. To investigate the relationship between assessment tools and biopsy result. Method: 100 consecutive patients who received a transperineal biopsy between January and June 2021 in Lister Hospital completed a questionnaire. Their investigation results were recorded, and data analysed. Results: Complication rates revealed 10% sustained heavy bleeding, 2% went into urinary retention, and 2% were treated with antibiotics for suspected urinary tract infection. Erectile dysfunction was not included on the questionnaire, however 4% raised this as a concern. Average number of cores appeared to be higher in those with complications compared to the whole sample. Pain score generally decreased with age, over 75s averaged 3.9/10 whilst under 65s averaged as 5.4/10. High PSA density and high PIRADS scores are well correlated with risk of positive biopsy PIRADS 2 was an exception to this trend, showing 14% had Gleason >6 compared with 9% in PIRADS 3. Not all PIRADS 2 patients will routinely receive a biopsy and therefore this could be down to preselection bias. All Gleason >6 cases in PIRADS 2 and PIRADS 3 had PSA density >0.15. Conclusions: Overall complication rate is low with no readmissions. The procedure is tolerated reasonably well and 85% would be willing to have the procedure again. Possible correlation between number of cores and complications. High PSA density and high PIRADS scores are well correlated with risk of positive biopsy. PIRADS 3 with low PSA density have a low proportion of positive biopsy.